POLITIK KANDIDASI CALON KEPALA DAERAH DI PARTAI POLITIK - Anggoro, Teguh; Mulyatin, Tina Cahya; Fadli, Andi Muh. Dzul (Universitas Medan Area, 2025)
Political recruitment within the Party can be less transparent. The recruitment process sometimes does not pay attention to the quality of the candidates. This study aims to analyze political recruitment related to the quality of candidates in the 2017 Regional Elections in Tasikmalaya City. The theory used in this study is the candidate quality theory (Jacobson & Kernell, 2006). This study uses a qualitative method with a phenomenological study approach. Data was collected through in-depth interviews, document studies, and literature studies. The informants in this study are PAN elites and cadres in TasikmalayaCity, DPW/DPP PAN cadres, and political observers in Tasikmalaya City. The study results explain that PAN deputy mayor candidates have low candidate quality. The findings in this study explain that PAN recruits candidates for mayor and deputy mayor of Tasikmalaya differently. The candidate for mayor of Tasikmalaya from PAN is recruited based on the quality of suitable candidates, while the candidate for deputy mayor is recruited due to financial strength. The difference was made because the candidate's considerable financial strength affected the party leadership. This resulted in the split support of party cadres in the regional elections. Seeing such problems, a transparent and merit-based recruitment process is needed. This research further strengthens the idea that the political recruitment process dramatically affects the internal dynamics of political parties.